The interpersonal dimension of psychopathology - O'Dowd, S A (Rhodes University, Faculty of Humanities, Department of Psychology, 1987)
It is argued that two large groups of disorders can be distinguished in the field of psychopathology, (1) which divide between them the psychoses, neuroses and personality disorders; ( 2) the dynamics of which are those of Klein's paranoid-schizoid and depressive positions, respectively; and (3) which are distinguished by nine basic contrasts in symptomatology and dynamics, all of which are expressive of the opposition self-centred/other-centred. These three hypotheses form the interpersonal model of psychopathology, and are supported by argument from works of Foulds, Jung, Abraham, Fairbairn, Klein, Angyal, Winnicott and Heidegger. It is suggested that the interpersonal model can facilitate the dialogue between psychoanalysis and phenomenology
Keywords: Psychology, Pathological